Autoimmune Gastrointestinal Paralysis: Failure of Conventional Treatment without Immunomodulation - Craig Weinkauf; Sean McPhillips; Robert Krouse; Ira Levine (Case Reports in Surgery)
The treatment of the rare enteric nervous system (ENS) manifestations of paraneoplastic syndromes, which are most frequently associated with small cell lung cancer (SCLC), is poorly understood and described. Patients with neuroendocrine-derived tumors can develop B-cell reactivity towards the tumor with cross-reactivity for neurons located in the submucosal and myenteric ganglia of the ENS. The ensuing autoimmune neuritis causes aperistalsis and severe gastrointestinal (GI) dysfunction. Immune-directed therapy is not the standard of care but may be paramount for patient recovery. Our patient, a 63-year-old man with recent symptoms of esophageal dysmotility and newly diagnosed SCLC was hospitalized with nausea, emesis, and constipation. After an extensive work-up that included laparoscopy and celiotomy with bowel resection, we diagnosed what we refer to as Autoimmune Paraneoplastic Chronic Intestinal Pseudoobstruction (AP-CIPO). Unlike the few clinically similar reports, SCLC and AP-CIPO were diagnosed in our patient within weeks of each other, which presented the dilemma of treating the two processes simultaneously. In this report, we review the relevant literature and describe our patient’s course. We believe standard chemotherapy is not effective treatment for AP-CIPO. Based on evidence discussed herein, we suggest initiating autoimmune-directed therapy before or simultaneous with cancer-directed therapy.